2016
DOI: 10.1371/journal.pone.0163321
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial Mfd Protein Prevents DNA Damage Induced by the Host Nitrogen Immune Response in a NER-Independent but RecBC-Dependent Pathway

Abstract: Production of reactive nitrogen species is an important component of the host immune defence against bacteria. Here, we show that the bacterial protein Mfd (Mutation frequency decline), a highly conserved and ubiquitous bacterial protein involved in DNA repair, confers bacterial resistance to the eukaryotic nitrogen response produced by macrophage cells and during mice infection. In addition, we show that RecBC is also necessary to survive this stress. The inactivation of recBC and mfd genes is epistatic showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…Archaeal Spt5, homologous to bacterially encoded NusG, consists of two domains: the NusG N-terminal (NGN) domain and a single C-terminal Kyrpides-Ouzounis-Woese (KOW) domain with affinity for single-stranded RNA (71,72,77); eukaryotic Spt5 typically contain three to six repeats of the C-terminal KOW domain (9,79,80). Critical, direct molecular interactions between Spt5 and RNAP have been identified in both Bacteria and Archaea, and the conservation of RNAP and Spt5 infers that these same interactions are used in Eukarya.…”
Section: Regulation Of Transcription Elongationmentioning
confidence: 99%
“…Archaeal Spt5, homologous to bacterially encoded NusG, consists of two domains: the NusG N-terminal (NGN) domain and a single C-terminal Kyrpides-Ouzounis-Woese (KOW) domain with affinity for single-stranded RNA (71,72,77); eukaryotic Spt5 typically contain three to six repeats of the C-terminal KOW domain (9,79,80). Critical, direct molecular interactions between Spt5 and RNAP have been identified in both Bacteria and Archaea, and the conservation of RNAP and Spt5 infers that these same interactions are used in Eukarya.…”
Section: Regulation Of Transcription Elongationmentioning
confidence: 99%
“…For example, they are important for the infectivity and pathogenicity of bacteria that need to resist oxidative and nitrosative attack from neutrophils and macrophages (Amundsen et al, 2008; Darrigo et al, 2016; Amundsen et al, 2009; Cano et al, 2002). They protect cells from antibacterials that cause DSBs, such as ciprofloxacin, because they afford a basal level of protection against such damage (Amundsen et al, 2009; Henderson and Kreuzer, 2015; González-Soltero et al, 2015; Tamae et al, 2008; McDaniel et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the bacteria have developed means to resist to the inflammatory cells and thus to the host immune system. We have consistently shown that B. cereus is able to circumvent the host immune response ( Tran and Ramarao, 2013 ; Darrigo et al, 2016 ; Guillemet et al, 2016 ). B. cereus spores survive, germinate, and multiply in contact with macrophages ( Ramarao and Lereclus, 2005 ), eventually leading to the production of toxins responsible for macrophage death ( Tran et al, 2011a , b ; Ramarao and Sanchis, 2013 ).…”
Section: Discussionmentioning
confidence: 82%